The Influence of Promotion on the Public's Interest in Becoming Customers at KSPPS BMT NU Branch Karang Penang - Hidayat, Muhammad Taufiq; Rohman, Abd.; Busro, Busro; Ferdiansyah, Mudi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Analyzing the influence of promotions on people's interest in becoming customers at KSPPS BMT NU Karang Penang Branch. The research was conducted using a qualitative approach, with a case study type of research. Data collection techniques were carried out using observation, interviews and documentation methods. Meanwhile, checking the validity of the data uses technical triangulation. The research results show that the strategy developed is: First, providing various types of products in a complex manner. Second, build relationships by holding regular meetings in priority areas that have great prospects in carrying out marketing. Third, strengthen relationships and collaborate with certain agencies or institutions on certain activities to maintain relationships with customers. Fourth, provide pick-up and drop-off services to make it easier for customers to carry out transactions. Fifth, attend several educational institution activities to maintain family relationships and maintain emotional ties with customers. The implications are, it is able to attract the interest of potential customers to carry out transactions and increase the loyalty of existing customers towards BMT NU because of the formation of trust and a sense of comfort with the relationships built. So that prospective customers built by BMT NU provide good fed back.